Understanding Edwin Thumboo - Sui, Singapore, Gwee Li (Asiatic: IIUM Journal of English Language and Literature, 2013)
Edwin Thumboo is arguably the most famous and powerful figure in Singaporean literature. He is also the most controversial, generating a broad range of responses to the meaning and value of his verse. Thumboo’s poetry parallels not just the stages of his life but problematically also how Singapore has developed socio-politically. These inextricable aspects create the very possibility for conflicting readings, which essentially disagree over historical decisions, the role of art and the impact of Thumboo’s career and character. My essay will look at the construction of the image of Thumboo and its relation to these differing outlooks. I shall consider the dimensions of his historical place, his artistic convictions, his status in literary and academic culture and his own personality. A different way of working with Thumboo – without using him to frame Singaporean literature – is also proposed. My wish is to be able to confront objectively where this major poet’s legacy stands today.